Bioactive compounds from marine extremophiles - Giddings, Lesley-Ann; Newman, David J. (SpringerBriefs in Microbiology,, 2015)
This SpringerBrief sheds new light on bioactive materials from marine extremophiles. It deals with all aspects of the chemical compounds produced by organisms living under extreme conditions that may have potential as drugs or lead to novel drugs for human use.